Nanostructures and Nanomaterials for Batteries Principles and Applications - Guo, Yu-Guo.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the roles of nanostructures and nanomaterials in the development of battery materials for state-of-the-art electrochemical energy storage systems, and provides detailed insights into the fundamentals of why batteries need nanostructures and nanomaterials. It explores the advantages offered by nanostructure electrode materials, the challenges of using nanostructured materials in batteries, as well as the rational design of nanostructures and nanomaterials to achieve optimal battery performance. Further, it closely examines the latest advances in the application of nanostructures and nanomaterials for future rechargeable batteries, including high-energy and high-power lithium ion batteries, lithium metal batteries (Li-O2, Li-S, Li-Se, etc.), all-solid-state batteries, and other metal batteries (Na, Mg, Al, etc.). It is a valuable reference resource for readers interested in or involved in research on energy storage, energy materials, electrochemistry and nanotechnology.
General introduction to electrochemical energy storage -- Fundamentals of nanostructures and nanomaterials for batteries -- Nanostructures and nanomaterials for lithium-ion batteries -- Nanostructures and nanomaterials for lithium metal batteries (Li-O2, Li-S, Li-Se, etc.) -- Nanostructures and nanomaterials for all-solid-state batteries -- Nanostructures and nanomaterials for other metal batteries (Na, Mg, Al, etc.) -- Traditional nanostructures for batteries.-Conclusions and perspectives.
Keywords: Materials; Catalysis; Force and energy; Energy storage; Electrochemistry; Nanotechnology; Materials for Energy and Catalysis; Mechanical and Thermal Energy Storage; Electrochemistry; Nanotechnology